Ada Cambridge’ s Subversive Romance - Klepač, Tihana (2009)
Suffering “ cultural apartheid” (Anne Summers) as a writer of urban romance novels in the predominantly male, realist, nationalist tradition of Australia, the work of Ada Cambridge has long been silenced, devalued, and given only documentary value by most literary critics. A careful analysis of A Marked Man, however, reveals Cambridge’ s subversion of both the form and the and content of the romance genre and thus proves its literary merit by producing an alternative to the nationalist metanarrative: a “ little narrative” (Lyotard) which voices the concerns of urban nineteenth-century Australian women.
Projekt MZOS
ENG